Canagliflozin Delays Aging of HUVECs Induced by Palmitic Acid via the ROS/p38/JNK Pathway - Wenhui Hao; Wenjie Shan; Fang Wan; Jingyi Luo; Yaoyun Niu; Jin Zhou; Yaou Zhang; Naihan Xu; Weidong Xie (MDPI AG, 2023)
Vascular aging is an important factor contributing to cardiovascular diseases, such as hypertension and atherosclerosis. Hyperlipidemia or fatty accumulation may play an important role in vascular aging and cardiovascular diseases. Canagliflozin (CAN), a sodium-glucose cotransporter inhibitor, can exert a cardiovascular protection effect that is likely independent of its hypoglycemic activities; however, the exact mechanisms remain undetermined. We hypothesized that CAN might have protective effects on blood vessels by regulating vascular aging induced by hyperlipidemia or fatty accumulation in blood vessel walls. In this study, which was undertaken on the basis of aging and inflammation, we investigated the protective effects and mechanisms of CAN in human umbilical vein endothelial cells induced by palmitic acid. We found that CAN could delay vascular aging, reduce the secretion of the senescence-associated secretory phenotype (SASP) and protect DNA from damage, as well as exerting an effect on the cell cycle of senescent cells. These actions likely occur through the attenuation of the excess reactive oxygen species (ROS) produced in vascular endothelial cells and/or down-regulation of the p38/JNK signaling pathway. In summary, our study revealed a new role for CAN as one of the sodium-dependent glucose transporter 2 inhibitors in delaying lipotoxicity-induced vascular aging by targeting the ROS/p38/JNK pathway, giving new medicinal value to CAN and providing novel therapeutic ideas for delaying vascular aging in patients with dyslipidemia.